Does timing of oral contraceptive pill intake affect physical performance-related parameters? A randomized crossover-controlled study - Bisgaard, M. S.; Josefsen, M. E.; Rasmussen, K. D.; Hansen, M. (International Journal of Sports Physiology and Performance, 2025)
Purpose: This study aimed to investigate whether maximal oxygen uptake, strength, and power parameters are influenced by the timing of oral contraceptive (OC) pill intake - specifically 1 versus 24 hours before testing.